Customer Based Brand Equity, Equity Drivers, and Customer Loyalty in the Supermarket Industry of Kathmandu Valley - Shrestha, Priya (Nepalese Journal of Economics, 2025)
This study examines the customer based brand equity, equity drivers, and customer loyalty in the supermarket industry of Kathmandu Valley. Customer loyalty is the dependent variable. The selected independent variables are brand price, brand value, brand quality, brand trust, and brand equity. The primary source of data is used to assess the opinions of respondents regarding brand price, brand value, brand quality, brand trust, and brand equity. The study is based on primary data. The primary data were gathered from 154 respondents through questionnaires. The correlation and multiple regression models are estimated to test the significance and importance of customer based brand equity, equity drivers, and customer loyalty in the supermarket industry of Kathmandu Valley. The study showed that brand price is positively correlated to customer loyalty. It indicates that affordable brand price leads to increase in customer loyalty. Similarly, brand quality is positively correlated to customer loyalty. It indicates that higher the brand quality, higher would be the customer loyalty. Likewise, brand value is positively correlated to customer loyalty. It indicates that higher the brand value, higher would be the customer loyalty. Further, brand trust is also positively correlated to customer loyalty. It indicates that higher the brand trust, higher would be the customer loyalty. In addition, brand equity is positively correlated to customer loyalty. It indicates that higher the brand desirability, higher would be the customer loyalty.